Formulation and Analysis of Millennia Nutrition Content (Anti-Anemia Jelly Drink) to Increase Hemoglobin Levels in Young Girls - Koka, Ecia Meilonna; Khairani, Fitri (Journal of Applied Science, Engineering, Technology, and Education, 2023)
Anemia is a nutritional problem in young women that needs to be prevented and addressed because it will impact the First 1000 Days of Life (HPK) period. Creating functional food products in the form of contemporary drinks that are nutritious and liked by teenagers is very important as an alternative to preventing anemia. Delays in early treatment of anemia have an impact on women experiencing pregnancy, which can cause bleeding complications during childbirth, giving birth to babies with low body weight and stunting. This condition must be treated as early as possible, because anemia in young women can indirectly affect the quality of human resources in the future. The purpose of this study was to find out how the Formulation and Analysis of the Nutritional Content of Millenia (Anti-Anemia Jelly Drink) to Increase Hemoglobin Levels in Young Girls. This type of research is experimental research, using a completely randomized study design consisting of three factors, in this case the researchers used three treatments, namely red guava juice with the addition of moringa leaf jelly and beet jelly using the symbols A1, A2 and A3. In treatment A1, red guava fruit juice, honey, moringa leaf jelly, and beetroot jelly were added at the respective doses of 200 ml, 20 gr, 10 gr, 20 gr. This drink is expected to be a drink that is rich in iron and other nutrients that can increase hemoglobin levels in the blood and is liked by teenagers because it is made like a contemporary drink that is currently a trend